Early-Middle Bronze Age communities and wood resources management in northeast Portugal: The Sabor valley - Martín-Seijo, María (2018)
This paper focuses on the relationship between human communities and wood resources in the Sabor valley (Trás-os-Montes region, northeast Portugal) during the Early and Middle Bronze Age. Charcoal from three archaeological sitesdTerraço das Laranjeiras, Foz do Medal and Quinta de Crestelosdwas analysed. As in other Early-Middle Bronze Age sites inWestern Iberia, the majority of the samples were recovered from pits, which complicates charcoal debris interpretation. The charcoal analysis suggests that the formation processes of the archaeobotanical record involved both natural and anthropic factors. The charcoal assemblages studied showed that taxonomic variability was strongly conditioned by the number of fragments produced per feature. Hearths, pits and post-holes provided information about the consumption of wood resources, highlighting the importance of taxa such as Fraxinus sp. and Quercus spp. combined with shrubby species including small trees (Juniperus sp., Arbutus unedo, Fabaceae, Cistus sp. and Erica spp.) and attesting the presence of Olea europaea within Middle Bronze Age contexts.